Development of Web-based Information Media in the Information Systems and Technology Education Study Program at the Indonesian Education University - Rasyad Amhar; Nuur Wachid Abdul Majid (Sistemasi: Jurnal Sistem Informasi, 2024)
The development of information technology is currently progressing quite rapidly, one implementation of this progress is the creation of web pages or what is known as the web. The web makes it easier for people to disseminate information so that it has an impact on people's activities in meeting their needs for information, including information about study programs (prodi). The Information Systems and Technology Education Study Program is one of the study programs at the Indonesian University of Education, Purwakarta regional campus, which currently cannot publish good information related to the study program itself. Therefore, an information media is needed to be able to publish information as a whole to the wider community. The method used in development is the waterfall method, and the technology used during development includes PHP Laravel, MySQL, PhpMyAdmin, Apache Server, and Visual Studio Code. The results of this research are in the form of a web-based information system that can better present information related to Education Systems and Information Technology study programs..